Predicting Functional Connectivity From Observed and Latent Structural Connectivity via Eigenvalue Mapping - Cummings, Jennifer A.; Sipes, Benjamin; Mathalon, Daniel H.; Raj, Ashish (Frontiers in Neuroscience, 2022)
Understanding how complex dynamic activity propagates over a static structural network is an overarching question in the field of neuroscience. Previous work has demonstrated that linear graph-theoretic models perform as well as non-linear neural simulations in predicting functional connectivity with the added benefits of low dimensionality and a closed-form solution which make them far less computationally expensive. Here we show a simple model relating the eigenvalues of the structural connectivity and functional networks using the Gamma function, producing a reliable prediction of functional connectivity with a single model parameter. We also investigate the impact of local activity diffusion and long range interhemispheric connectivity on the structure-function model and show an improvement in functional connectivity prediction when accounting for such latent variables which are often excluded from traditional DTI methods.